Good code, bad code : think like a software engineer - Long, Tom (Software engineer) (Manning, 2021)
"Software development is a team sport. For an application to succeed, your code needs to be robust and easy for others to understand, maintain, and adapt. Whether you're working on an enterprise team, contributing to an open source project, or bootstrapping a startup, it pays to know the difference between good code and bad code. Good Code, Bad Code is a clear, practical introduction to writing code that's a snap to read, apply, and remember"--Page 4 of cover